"Spots of Time" – Michael Wessels and the Imaginative Reinterpretation of Identity. Issue 2 (3rd July 2021) - Moolman, Kobus
Abstract : For Linzi, Akira and Tao While much of Michael Wessels's work on reading San oral literature, the politics of indigeneity and ecocriticism was acknowledged during his life, there is another dimension to his research that has been overlooked. Michael Wessels always had a deep love of poetry, and toward the end of his life, he had begun to focus more on his writing and to publish. In this article, I explore Wessels's key long poem published as "Cannibal Time, " but subsequently changed to "Spots of Time" (as I will refer to it), in which he constructs an imaginative autobiography that includes travel writing, short prose and poetry. Drawing upon Wordsworth's The Prelude, I employ both a critical and creative methodology to argue that the subject of Wessels's poem is less 'my life' in a factual and historical sense, and rather more 'the making of a poet'.